2007
DOI: 10.1308/003588407x179125
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Phase III Clinical Trials of Prostate Cancer Chemoprevention

Abstract: Prostate cancer is now the most common nondermatological male malignancy and is the second most common cause of male cancer related death in the UK; approximately 1 in 14 men in the UK will be diagnosed with prostate cancer in their life-time.1 Prostate cancer is strongly associated with increasing age, with the mean age of onset being 72-74 years 2 and 96% cases occurring in men over 60 years.3 Cancer chemoprevention can be thought to include reversal and delay of carcinogenesis, in addition to prevention. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 31 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…[29] Finasteride is the only intervention that has been shown to reduce the incidence of prostate cancer in a long-term prospective clinical trial. [30]…”
Section: Discussionmentioning
confidence: 99%
“…[29] Finasteride is the only intervention that has been shown to reduce the incidence of prostate cancer in a long-term prospective clinical trial. [30]…”
Section: Discussionmentioning
confidence: 99%
“…23 The recently completed REDUCE trial indicated that dutasteride, a more comprehensive 5ARI than finasteride (that is, both isoenzymes), reduced prostate cancer risk by 23% within 4 years. 20,21,24 If such therapies are found to be both safe and effective, they may also represent an opportunity to reduce the impact of costly prostate cancer treatment interventions, not only in economic Clinical and economic burden of prostate cancer ED Crawford et al…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that prostate cancer incidence may be reduced by chemopreventive strategies (3). Selenium is an essential element in maintenance of the activity of some antioxidant enzymes and redox-regulatory proteins.…”
Section: Introductionmentioning
confidence: 99%